2018
DOI: 10.1186/s41182-018-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of virulence gene profiles and genomic fingerprints of Vibrio cholerae O1 and non-O1/non-O139 isolates from diarrheal patients in southern Thailand

Abstract: BackgroundVibrio cholerae is associated with severe watery diarrheal disease among people in many parts of the world, including the coastal provinces of Southern Thailand. There are relatively few studies focusing on the genetic characterization among V. cholerae isolates in this region. Therefore, this study aimed at exploring the presence of virulence genes and DNA fingerprints among V. cholerae O1 and non-O1/non-O139 isolates obtained from clinical samples in four southern coastal provinces during the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“… 60 The ERIC-PCR has been applied in clonal diversity and genotyping of V. cholerae isolates from clinical and environmental origins. 6 , 18 , 61 , 62 For instance, Xu et al reported 328 ERIC-genotypes among 400 V. cholerae isolates derived from 4 species of fish. 18 In this study, the 370 V. cholerae isolates recovered from the 12 species of aquatic products were classified into 239 ERIC-genotypes, 69.9% of which were assigned as singletons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 60 The ERIC-PCR has been applied in clonal diversity and genotyping of V. cholerae isolates from clinical and environmental origins. 6 , 18 , 61 , 62 For instance, Xu et al reported 328 ERIC-genotypes among 400 V. cholerae isolates derived from 4 species of fish. 18 In this study, the 370 V. cholerae isolates recovered from the 12 species of aquatic products were classified into 239 ERIC-genotypes, 69.9% of which were assigned as singletons.…”
Section: Discussionmentioning
confidence: 99%
“…The major virulence genes ( ctxAB and tcpA ) (Kumar et al ) 33 and virulence-associated genes ( ace , zot , rtxABCD , hapA , hlyA , tlh , mshA , and pilA ). 6 , 11 , 18 , 34 were detected by PCR assay using the primer pairs listed in Table 1 . The PCR reaction conditions varied depending on the melting temperature (Tm) values of the primer pairs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The virulence and virulence-associated genes ctxAB , tcpA , ace , zot , rtxCABD , hapA , hlyA , tlh , mshA , and pilA were detected by PCR assay using the oligonucleotide primers [ 6 , 48 , 49 , 50 , 51 , 52 ] listed in Table S4 . PCRs were performed as described previously [ 6 ].…”
Section: Methodsmentioning
confidence: 99%